Exploring the patterns of matching the demand and supply of skills and immigration in the destination countries : Lithuania, Poland, Germany, France, Italy, the United Kingdom and Norway : synthesis report WP2 - Winterton, Jonathan [Verfasser] (My University, 2025)
"This Report presents the findings of the comparative research of the patterns of matching the demand and supply of skills and immigration in the destination countries - Lithuania, Poland, Germany, France, Italy, the United Kingdom and Norway executed in the framework of the Horizon Europe project 'SKILLS 4 JUSTICE: Skill Partnerships for Sustainable and just Migration Patterns' in 2024. The Horizon project Skills4Justice investigates labour and skills shortages in the European area and the extent to which these are being addressed through employing migrant workers from beyond the European area. The destination countries include five EU member states (France, Germany, Italy, Lithuania and Poland) and two non-EU European countries (Norway and the UK). These seven countries differ considerably in terms of labour market regulatory frameworks, skill formation systems and immigration policies, the combinations of which create specific country contexts that are briefly reviewed in this Introduction, drawing on the national reports produced by country teams." (Authors' abstract, BIBB-Doku)
Keywords: G 1.2.3 Qualifikationsentwicklungen; G 1.2.3.2 Anforderungen & Bedarfe; P 1.5 Migranten; I 2.2.1 Westeuropa; I 2.2.2 Osteuropa; 370; Berufliche Qualifikation; Mismatch; Unterqualifikation; Überqualifikation; Fachkräftebedarf; Fachkräftemangel; Einwanderer; Internationaler Vergleich; Bundesrepublik Deutschland; Frankreich; Italien; Litauen; Norwegen; Polen; Vereinigtes Königreich